Expression of mRNAs for pro-and anti-apoptotic factors in granulosa cells and follicular fluid of women undergoing in vitro fertilization. A pilot study - József Bódis; Endre Sulyok; Ákos Várnagy; Viktória Prémusz; Krisztina Gödöny; Alexandra Makai; Ágnes Szenczi; Timea Varjas (BMC, 2021)
Abstract Background This observational clinical study evaluated the expression levels and predictive values of some apoptosis-related genes in granulosa cells (GCs) and follicular fluid (FF) of women undergoing in vitro fertilization (IVF). Methods GCs and FF were obtained at oocyte retrieval from 31 consecutive patients with heterogeneous infertility diagnosis (age: 34.3 ± 5.8 years, body mass index: 24.02 ± 3.12 kg/m2, duration of infertility: 4.2 ± 2.1 years). mRNA expression of pro-apoptotic (BAX, CASP3, CASP8) and anti-apoptotic (BCL2, AMH, AMHR, FSHR, LHR, CYP19A1) factors was determined by quantitative RT-PCR using ROCHE LightCycler 480. Results No significant difference in GC or FF mRNA expression of pro- and anti-apoptotic factors could be demonstrated between IVF patients with (9 patients) or without (22 patients) clinical pregnancy. Each transcript investigated was detected in FF, but their levels were markedly reduced and independent of those in GCs. The number of retrieved oocytes was positively associated with GC AMHR (r = 0.393, p = 0.029), but the day of embryo transfer was negatively associated with GC LHR (r = − 0.414, p = 0.020) and GC FSHR transcripts (r = − 0.535, p = 0.002). When pregnancy positive group was analysed separately the impact of apoptosis- related gene expressions on some selected measures of IVF success could be observed. Strong positive relationship was found between gene expression levels of pro- and anti-apoptotic factors in GCs. Conclusion Our study provides only marginal evidences for the apoptosis dependence of IVF outcome and suggests that the apoptosis process induces adaptive increases of the anti-apoptotic gene expression to attenuate apoptosis and to protect cell survival.